Parent Perceptions on Parenting Consultation Services at Kindergarten Sahabat Ananda Malang District - Andhini Dwi Saputri; Edi Widianto (International Research-Based Education Journal, 2021)
This research is generally aimed to know the perception of parent to the implementation of parenting consultation service program at PAUD institution Sahabat Ananda, as well as special purpose to know parent perception on implementation of parenting consultation service program from cognitive aspect, affective aspect, and connective aspects. Suggestion given in research 1) It is expected that the school can provide knowledge to parents about how to face and take care of the child, 2) For parents are expected to improve their participation in the parenting program, and 3) It is expected next researcher to conduct research with a wider scope, especially those relating to the program of parenting.